Laughter is in the air: involvement of key nodes of the emotional motor system in the anticipation of tickling. Issue 8 (8th August 2019) - Wattendorf, Elise; Westermann, Birgit; Fiedler, Klaus; Ritz, Simone; Redmann, Annetta; Pfannmöller, Jörg; Lotze, Martin; Celio, Marco R
Abstract: In analogy to the appreciation of humor, that of tickling is based upon the re-interpretation of an anticipated emotional situation. Hence, the anticipation of tickling contributes to the final outburst of ticklish laughter. To localize the neuronal substrates of this process, functional magnetic resonance imaging (fMRI) was conducted on 31 healthy volunteers. The state of anticipation was simulated by generating an uncertainty respecting the onset of manual foot tickling. Anticipation was characterized by an augmented fMRI signal in the anterior insula, the hypothalamus, the nucleus accumbens and the ventral tegmental area, as well as by an attenuated one in the internal globus pallidus. Furthermore, anticipatory activity in the anterior insula correlated positively with the degree of laughter that was produced during tickling. These findings are consistent with an encoding of the expected emotional consequences of tickling and suggest that early regulatory mechanisms influence, automatically, the laughter circuitry at the level of affective and sensory processing. Tickling activated not only those regions of the brain that were involved during anticipation, but also the posterior insula, the anterior cingulate cortex and the periaqueductal gray matter. Sequential or combined anticipatory and tickling-related neuronal activities may adjust emotional and sensorimotor pathways in preparation for the impending laughter response.